Donor-specific Antibodies, Immunoglobulin-free Light Chains, and BAFF Levels in Relation to Risk of Late-onset PTLD in Liver Recipients. Issue 6 (June 2018) - Engels, Eric A.; Jennings, Linda W.; Everly, Matthew J.; Landgren, Ola; Murata, Kazunori; Yanik, Elizabeth L.; Pfeiffer, Ruth M.; Onaca, Nicholas; Klintmalm, Goran B.
Abstract : Background: Posttransplant lymphoproliferative disorder (PTLD) is a neoplastic complication of transplantation, with early cases largely due to immunosuppression and primary Epstein-Barr virus infection. Etiology may differ for later-onset cases, but the contributions of immunosuppression, immune reactivity to the donor organ, and chronic B cell activation are uncertain. Methods: We conducted a case-control study of late-onset PTLD (diagnosed >1 year posttransplant) in a cohort of liver recipients. We assessed serum samples (obtained >6 months before diagnosis in cases) from N = 60 cases and N = 166 matched controls for donor-specific antibodies (DSAs, evaluable for N = 221 subjects), immunoglobulin kappa and lambda free light chains (FLCs, N = 137), and B cell activating factor (BAFF, N = 226). Conditional or unconditional logistic regression was used to calculate adjusted odds ratios (aORs). Results: Circulating DSAs were less common in PTLD cases than controls (18% vs 30%), although this difference was borderline significant (aOR, 0.51; 95% confidence interval [CI], 0.24-1.10; P = 0.09). Donor-specific antibodies against class II HLA antigens predominated and likewise showed a borderline inverse association with PTLD (aOR, 0.58; 95% CI, 0.27-1.24). The FLC levels were less frequently abnormal in cases than controls, but measurements were available for only a subset and confidence intervals were wide (elevated kappa: aOR, 0.57; 95% CI, 0.15-2.12; P = 0.40; elevated lambda: aOR, 0.68; 95% CI, 0.30-1.50; P = 0.34). B cell–activating factor levels were not associated with PTLD. Conclusions: Our results suggest that circulating DSAs are associated with decreased risk of late-onset PTLD. Because DSAs may develop in the setting of underimmunosuppression, the inverse association with DSAs supports a role for immunosuppression in the etiology of late-onset PTLD.